Effect of Techno-Entrepreneurial Relationship Marketing on Marketing Performance and Competitive Advantage - Irin Mirrah Luthfia; Sri Eka Sadriatwati; Mellasanti Ayuwardani; Rara Ririn Budi Utaminingtyas; Rustono (Admisi dan Bisnis, 2026)
The increasing intensity of digital competition requires entrepreneurial students to adopt innovative and technology-driven marketing strategies in order to sustain business performance and competitiveness. Techno-Entrepreneurial Relationship Marketing (TERM) has emerged as an integrated approach that combines technology utilization, entrepreneurial orientation, and relationship-based marketing practices. This study aims to examine the effect of Techno- Entrepreneurial Relationship Marketing on Marketing Performance and its implication for Competitive Advantage among entrepreneurial students. The research employs a quantitative approach using survey data collected from entrepreneurial students of the Business Administration Department. Structural Equation Modeling (SEM) with AMOS is utilized to test the proposed hypotheses. The results indicate that Techno-Entrepreneurial Relationship Marketing has a positive and significant effect on Marketing Performance. Furthermore, Marketing Performance is found to have a significant positive influence on Competitive Advantage. These findings suggest that Marketing Performance plays a mediating role in translating techno-entrepreneurial relationship marketing practices into sustainable competitive advantage. The study contributes to the development of entrepreneurial marketing literature and provides practical implications for higher education institutions in strengthening students’ entrepreneurial competitiveness.